2014
DOI: 10.1158/1078-0432.ccr-13-3044
|View full text |Cite
|
Sign up to set email alerts
|

NADPH Oxidases as Therapeutic Targets in Chronic Myelogenous Leukemia

Abstract: Purpose: Cancer cells show higher levels of reactive oxygen species (ROS) than normal cells and increasing intracellular ROS levels are becoming a recognized strategy against tumor cells. Thus, diminishing ROS levels could be also detrimental to cancer cells. We surmise that avoiding ROS generation would be a better option than quenching ROS with antioxidants. Chronic myelogenous leukemia (CML) is triggered by the expression of BCR-ABL kinase, whose activity leads to increased ROS production, partly through NA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 42 publications
(53 reference statements)
6
41
0
Order By: Relevance
“…Nuclei to the left of the 2N peak containing hypodiploid DNA were considered as apoptotic. Fluorescent microscopy and flow cytometric analysis of PI-stained nuclei were performed to evaluate cell cycle and viability by using a FACSCalibur cytometer and CellQuest software (BD Biosciences, Erembodegen, Belgium) [55]. Apoptosis was also determined by translocation of phosphatidylserine to the cell surface using the annexin V-FITC apoptosis detection kit (BD Pharmingen, Erembodegen, Belgium) according to the manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Nuclei to the left of the 2N peak containing hypodiploid DNA were considered as apoptotic. Fluorescent microscopy and flow cytometric analysis of PI-stained nuclei were performed to evaluate cell cycle and viability by using a FACSCalibur cytometer and CellQuest software (BD Biosciences, Erembodegen, Belgium) [55]. Apoptosis was also determined by translocation of phosphatidylserine to the cell surface using the annexin V-FITC apoptosis detection kit (BD Pharmingen, Erembodegen, Belgium) according to the manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we have shown that Mito-CP and other mitochondria-targeted antioxidants inhibit Nox2 expression and activity in mice and inhibit nitration and carbonylation of proteins induced by NADPH oxidases (Nox) and inducible NOS [44,45]. Nox enzymes are emerging as a highly promising target for anticancer drug development [8,9]. Increasing evidence suggests that Noxderived ROS inhibits tumor apoptosis and stimulates tumor proliferation [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Nox enzymes are emerging as a highly promising target for anticancer drug development [8,9]. Increasing evidence suggests that Noxderived ROS inhibits tumor apoptosis and stimulates tumor proliferation [8,9]. It is plausible that indirect inhibition of Nox enzymes by Mito-CP and Mito-CP-Ac contributes to inhibition of tumor cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NOX, particularly NOX4, have also been implicated in resistance to target therapies (Liu‐Smith et al , ; Sanchez‐Sanchez et al , ), anti‐hormonal therapies (Lu et al , ) and cytotoxics (Chang et al , ) as well as radiotherapy (Hsieh et al , ; Li et al , ), indicating that NOX inhibitors might enhance the efficacy of current cancer treatments.…”
Section: Multi‐organmentioning
confidence: 99%